1999
DOI: 10.3989/cyv.1999.v38.i6.910
|View full text |Cite
|
Sign up to set email alerts
|

Papel de la posición del electrodo de referencia en las medidas de sobrepotencial

Abstract: Steady state polarisation measurements can be affected by electrode microstructure and geometrical arrangement. In particular, the relative position of the reference electrode with respect to the working and counter electrodes may influence the reference potential and therefore effect the overvoltage readings. The influence of the geometrical arrangement of the electrodes on the electrolyte potential lines, was simulated by solving the appropriate Maxwell equations. Simulations were in relatively good agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20][21][22] Still, with proper care, the information that these experiments yield can be valuable for optimization of SOFC electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22] Still, with proper care, the information that these experiments yield can be valuable for optimization of SOFC electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…As has been discussed in detail in several previous studies, proper alignment of the cathode and anode and positioning of the reference electrode are required in order to obtain accurate measurements of overpotentials using both current interruption and impedance spectroscopy [9][10][11][12][13]. For a cell with an ideal configuration the magnitude of the initial drop in the reference to cathode current interruption measurement should be equal to that in the reference to anode measurement at the same current density.…”
Section: Resultsmentioning
confidence: 99%
“…The overpotential, A In order to completely separate the anode and cathode processes a well-placed reference electrode is again required. Several recent experimental and theoretical studies have demonstrated the importance of well-designed cell geometry in order to obtain a reference electrode whose potential is pinned near the center of the electrolyte and independent of cell current [9][10][11][12][13]. These studies show that one needs to use a cell with a relatively thick electrolyte, symmetric coaxial placement of the cathode and anode, and placement of the reference electrode at least three electrolyte thicknesses from the edge of one of the electrodes.…”
Section: Cu-ceria-ysz Cermet Anodes For Solid Oxide Fuel Cells (Sofcsmentioning
confidence: 99%
“…This factor may be controlled by an accurate design of the electrode geometry ensuring symmetrical electrode arrangements and keeping them at a convenient distance. Based on finite elements simulations of the potential distribution [14], this distance was found to be of 3-4 mm for a 1 mm thick electrolyte. Finally, an oxygen concentration gradient may occur between the sample inner surface and the pumping electrodes leading to a non-equilibrium sensor reading.…”
Section: Methodsmentioning
confidence: 99%